(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, the formation of mathematical knowledge and skills through fairy-tale problems and teaching elementary school students to successfully apply this knowledge in everyday life, the importance of mathematical fairy tales in children’s lives, what are the reasons for organizing lessons based on such fairy tales It is said that attention should be paid.